Mobile Robots and Autonomous Vehicle Control: A Comprehensive Review of the Advancements and Challenges - Tamakloe, Elvis; Kommey, Benjamin; Addo, Ernest Ofosu; Opoku, Daniel (Makara Journal of Technology, 2025)
Since their inception, mobile robots have enormously changed the landscape of robotics engineering in recent years. Imperatively, the impact of mobile robots has positively transformed many sectors of human endeavors, i.e., complemented and substituted humans in areas where human interactions were difficult, hazardous, and impossible to thrive and operate. In this regard, the contributions of mobile robots to scientific, social, and economic growth, development, and advancement cannot be overlooked, especially through its decades of transition from Industry 3.0 to 4.0 over the years. To achieve maximum benefits from the use of mobile robots across all important facets, their advancements and technologies need to be continuously improved to address all relevant issues with regard to associated challenges in navigation, control, remote sensing, and tele-operability. This paper presents a comprehensive review of selected key areas of mobile robot technology where major advancements have been made and are currently ongoing to solve numerous problems effectively with less human effort. In addition, highlights of the challenges faced by mobile robots and autonomous vehicle control have been extensively discussed and recommendations have been given to enhance the efficient and safe use of mobile robots in the event of a change in task complexity in all essentials of human life.